The Needs of Refugee and Asylum-Seeking Children in Thailand - Thoresen, Paradee (Curtin University, 2018)
This qualitative research investigated the needs of refugee and asylum-seeking children in the context of existing services and policies in Thailand. Observation, semi-structured interviews, and children’s drawings and writing were used to gather information in Mae Sot and Bangkok between 2014 and 2015, from 129 participants including 39 children and 90 adults. The results suggest existing laws and policies prevent children from meeting their needs. This could be remedied by considering children as global citizens.